1972
DOI: 10.3758/bf03328961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isolation, daily handling, and enriched rearing on maze learning

Abstract: Daily handling for 30 days after weaning reduced straight alley running time in isolated rats, but had no significant effect on Lashley III maze learning. Both handled and unhandled isolates were inferior in maze learning to littermates reared in an enriched environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Alternatively, if handling in adulthood reduces anxiety, then the enrichment-induced improvements may have resulted from daily transfers from the home cage to enrichment chamber. However, studies in rats have shown that handled and non-handled control rats are similarly impaired relative to EC rats (Greenough et al, 1972). Furthermore, we have recently noted that although handled (transferred daily to and from home cage) and non-handled (never removed from home cage) C57BL/6 male mice perform similarly on object recognition and water maze tasks, both groups perform significantly worse than EC mice (K. M. Frick, unpublished observations).…”
Section: Effects Of Enrichment Alonementioning
confidence: 98%
“…Alternatively, if handling in adulthood reduces anxiety, then the enrichment-induced improvements may have resulted from daily transfers from the home cage to enrichment chamber. However, studies in rats have shown that handled and non-handled control rats are similarly impaired relative to EC rats (Greenough et al, 1972). Furthermore, we have recently noted that although handled (transferred daily to and from home cage) and non-handled (never removed from home cage) C57BL/6 male mice perform similarly on object recognition and water maze tasks, both groups perform significantly worse than EC mice (K. M. Frick, unpublished observations).…”
Section: Effects Of Enrichment Alonementioning
confidence: 98%
“…In addition, IR rats demonstrate neophobia Gentsch et al 1982;Hall et al 1997b), increased timidity , increased anxiety (Wright et al 1991), and perseverative behaviours Dalrymple-Alford and Benton 1984). Moreover, IR seems to affect cognitive learning in diverse tasks (Greenough et al 1972;Gardner et al 1975;Holson 1986;Weiss et al 2001), although some conflicting results exist regarding the IR effect on spatial learning tasks (Wongwitdecha and Marsden 1996; G. Gregorian, I. Weiss and J. Feldon, unpublished observations). Finally, IR does not affect LI (Feldon et al 1990;Weiss et al 2001).…”
Section: Social Isolationmentioning
confidence: 99%
“…Animals exposed to an enriched or complex environment (EC) exhibit superior performance in learning and remembering place(s) in a variety of land-and water-based mazes compared with controls raised in standard laboratory cages in social (SC) groups (e.g., Greenough, Madden, & Fleischmann, 1972;Juraska, 1990;Seymoure, Dou, & Juraska, 1996;Tees et al, 1990). A lack of an early visual stimulation history has also been shown to adversely affect adult spatial working and reference memory in later tested (blind and sighted) rats (e.g., Tees, Midgley, & Nesbit, 1981).…”
mentioning
confidence: 99%